Study on the Structrual Parameter Coupling of Articulated Arm Coordinate Measuring Machines - Guanbin Gao; Jian Lu; Huiping Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The articulated arm coordinate measuring machine (AACMM) is a kind of new coordinate measuring device based on non-Cartesian system. The measuring accuracy of the AACMM can be effectively improved by parameter identification. However, some of the structural parameters are coupling (linearly related), so the structural parameters usually cannot be identified correctly. The Jacobian matrix was obtained through differential transformation of the kinematic model of a 6-DOF AACMM. The rank calculation results show that the Jacobian matrix is not full rank, which means some structural parameters are linearly related. Singular value decomposition and the elementary row transform of the Jacobian matrix were carried out to determine the linearly related structural parameters. And two pairs of structural parameters were found to be linearly related, which can’t be identified at the same time. Finally, the linear correlation was applied in the structural parameters identification, and the results show that the linear correlation can make the identification obtain correct structural parameters. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2474